INSPIRASI FISIKA MISTERI SEBAGAI PROBLEM SOLVING PEMBELAJARAN SAINS DALAM MENYONGSONG MEA - Handoyo Saputro (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2016)
The quality of education was the main condition to realize advanced, modern, and prosperous nation’s life which was determined by the quality of human resources. The quality of human resources itself was determined by the quality education at the basic, intermediate or advanced level. The education plays a key role in the effort to educate the nation lifes. The physics of mystery was an inspiration and new inovation of problem solving on the physics science learning to respond the challanges in welcoming MEA. To produce inovation learning, all of the learning components that include teachers, students, teaching materials, the achievments of competency, and learning evaluation need to be innovated. The point was the innovative physics science learning was learning that could equip accompaniment effects learning that include higher level thinking and generic phiysics science skills. A wide variety of advanced technology was the result, such as the technology of tranportation which made the humans could travel from one place to another easily and quickly. The technology would not be possible to develop andcreate without the fundamental of knowladge that supports it. The fundamental of knowladge was none other than science, particularly physics. In this paper, it would be shown about the new inspiration of innovative of physics learning as the problem solving of physics concept. It was the physics of mystery. The secret behind this inspiration could be one of solution to overcome the student difficulties in undertanding of physics concepts easily and quickly and also to respond the challanges of global competition (MEA).